Lactobacillus rhamnosus GG supplementation on eradication rate and dyspepsia in Helicobacter pylori infection treated with three-in-one bismuth quadruple therapy - Marinelli, Paride; Scalese, Giulia; Covelli, Antonio; Ruffa, Andrea; Bedetti, Giorgio; Bruno, Giovanni; Severi, Carola (Frontiers in Microbiology, 2022)
Introduction Helicobacter pylori (Hp)-related dyspepsia has been related to gastroduodenal dysbiosis. The role of probiotic supplementation in the clinical management of Hp infection has been the object of several studies in terms of improvement of efficacy and tolerability of eradication treatments but data on their effects on the outcomes of post-eradication dyspepsia are lacking. The aim of the present study was to evaluate the influence of Lactobacillus rhamnosus GG (LGG) supplementation on bismuth quadruple therapy (BQT) in the clinical management of Hp-related infection both in terms of efficacy and tolerability and persistence of post-treatment dyspepsia. Methods A total of 164 (121 women) Hp-positive adult patients were enrolled in this pilot study and assigned to two different treatment regimens: group A received BQT for 10 days (three capsules qid, IPP bid) and group B received BQT for 10 days in combination with 6 × 109CFU LGG (ATCC53103) taken for 24 days (7 days before, 10 days during, and 7 days after therapy). Eradication was assessed after 45 days using the 13C-urea breath test (13C-UBT). Dyspepsia, distinguished into postprandial distress syndrome (PDS) and epigastric pain syndrome (EPS), was assessed at the time of enrollment and 6 months after eradication. Results Approximately 98 patients were enrolled in group A and 66 patients in group B. At the enrollment, dyspepsia was present in 76.5% of group A and 86.5% of group B. No significant differences were observed in eradication rate between the 2 groups, both in intention-to-treat (ITT) analysis (82.3 vs. 75.0%) and per-protocol (PP) analysis (95 vs. 96%), and in the presence of side effects during the treatment (70.6 vs. 65.4%). At 6 months after eradication of Hp infection, the persistence of dyspepsia was statistically higher in patients of group A than in group B (38.8 vs. 16.1%; p = 0.032). The positive influence of LGG supplementation in improving post-eradication dyspepsia resulted in statistically more effectiveness in PDS dyspepsia, whose remission was 41.7% in group A and 84% in group B patients (p = 0.011). Conclusion In conclusion, LGG supplementation during Hp eradication therapy, even if not affecting eradication rates and therapy-related side effects, significantly impacts the remission of dyspepsia.